CVD growth of high-quality graphene over Ge (100) by annihilation of thermal pits. (15th April 2021) - Diallo, Thierno Mamoudou; Aziziyan, Mohammad Reza; Arvinte, Roxana; Arès, Richard; Fafard, Simon; Boucherif, Abderraouf
Abstract: The physical and chemical state of the underlying germanium (Ge) substrate is crucial for the CVD synthesis of high-quality graphene. Here, we investigate the main causes responsible for formation of pit-like defects on Ge (100) and (111) surfaces, their elimination, and their influence on the quality of deposited graphene. Our data provides evidence of pit-like defects formation on Ge surfaces during thermal annealing at T ≥ 800 °C. We establish that the pits are due to preferential evaporation of residual Ge suboxides, and that their efficient removal would result in a pit-free surface. Oxide removal on HF, HCl and HBr treated surfaces is investigated using X-ray photoemission spectroscopy (XPS). The results confirm that in contrast to HF and HCl, HBr effectively eliminates GeO2 and Ge suboxides, providing pit-free surfaces, which enable CVD growth of high-quality graphene. Hence, we demonstrate that effective elimination of Ge suboxides enables the synthesis of graphene monolayers with excellent quality (ID /IG ∼ 0.2) as confirmed by Raman spectroscopy measurements. The experimental data provides clear corroboration for the role played by the Ge suboxides in the formation of thermal pits and the control of the graphene quality. Our findings lay the foundation for Ge substrates cleaning and the synthesis of high-quality graphene films for advanced applications. Graphical abstract: Image 1